Editorial (English) - Abar, Celina A. A. Pereira; Oliveira, Gerson Pastre de (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2011)
The second themed issue of the Educação Matemática Pesquisa (Mathematics Education Research) journal - the third of three volumes in 2010 - is organized around the research line of Information Technology and Mathematics Education, a field of study that highlights the important role of technology in the teaching and learning of mathematics. From this point of view, the main subject in the call for articles was Technologies in Mathematics Education: contributions, reflexions and strategies. The presented papers aim to discuss different possibilities and ways in which this issue can be investigated, and also demonstrate the need for dissemination of new studies to allow researchers and teachers to find, in high quality publications, the support for their work.